(untitled) (Journal of Applied Oral Science, 2022)
Literature has reported positive results regarding the use of lasers in the control of erosive lesions; however, evaluating whether they are effective in the control of the progression of erosive/abrasive lesions is important. Objectives: This study aimed to evaluate the effect of the Er:YAG laser irradiation in controlling the progression of erosion associated with abrasive lesions in enamel. Material and methods: Bovine incisors were sectioned, flattened and polished. Forty-eight enamel slabs were subjected to treatment in an intraoral phase. Twelve volunteers used an intraoral appliance containing one slab that was irradiated with an Er:YAG laser (5.2 J/cm2, 85 mJ, 2 Hz) and another non-irradiated slab on each side of the appliance, during one phase of 5 d, under a split-mouth design. Devices were subjected to erosive challenges (1% citric acid, 5 min, 3 times a day) and abrasive challenges one h after (brushing force of 1.5 N for 15 s) randomly and independently on each side of the device. Measurements of enamel loss were performed via 3D optical profilometry (μm). We analyzed data using the Kruskal-Wallis and Mann-Whitney tests and morphological characteristics via scanning electron microscopy. Results: Following erosive and abrasive challenges, the group that was irradiated with the Er:YAG laser presented less loss of structure than the non-irradiated group. The group that underwent erosion and irradiation did not exhibit a significant difference from the non-irradiated group. Conclusion: Irradiation with the Er:YAG laser did not control the loss of structure of enamel subjected to erosion but did control abrasion after erosion.